2009
DOI: 10.1007/s10260-009-0128-x
|View full text |Cite
|
Sign up to set email alerts
|

A geostatistical approach to define guidelines for radon prone area identification

Abstract: Radon prone areas, Kriging, Geostatistical conditional simulation, Change of support problem,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 26 publications
(25 reference statements)
0
9
0
Order By: Relevance
“…Firstly this research can help in recommending some guidelines for new buildings. In Lombardy, as in many other regions around the world, mapping IRC is nowadays a common practice (see [3] for IRC mapping on the same data). Such maps inform people of where higher concentrations can be expected.…”
Section: Discussionmentioning
confidence: 99%
“…Firstly this research can help in recommending some guidelines for new buildings. In Lombardy, as in many other regions around the world, mapping IRC is nowadays a common practice (see [3] for IRC mapping on the same data). Such maps inform people of where higher concentrations can be expected.…”
Section: Discussionmentioning
confidence: 99%
“…The radon-prone area issue points at what is known as change of support problem (COSP) in geostatistical terminology (Arbia 1989), since a realignment of radon data is required from the point level, where the measurement process takes place, to the area or block level, i.e. the administrative unit of a town, where the remediation actions should be implemented (Borgoni et al 2010). A solution to point-to-block COSP is provided by block-kriging (Chiles and Delfiner 1999), a technique that allows for predicting the average of a spatial random field on a given area.…”
Section: Geostatistical and Bayesian Methods For Radon Mappingmentioning
confidence: 99%
“…3a). Several studies show a clear relationship between geological factors and indoor radon concentration; however other factors, to a lesser extent, such as soil structure, groundwater conditions, ventilation and condition of the building, and so on, defi nitely infl uence the measurements [16]. For our purposes, all these factors can be considered as a source of spatially uncorrelated noise.…”
Section: Simulated Radon Concentration Datasetmentioning
confidence: 99%
“…Although crucial to limit the uncertainty on the estimation of expected concentration, it was shown that identify the correlation trend and hence the parameters R and S from an indoor concentration measurement campaign is not a trivial process, in particular for sparse and noisy sampling. In the next Section, we present a new tool for the variogram computation based on the spatial variability of the Gini coeffi cient [15][16][17].…”
Section: The Semi-variance and The Variogrammentioning
confidence: 99%